Comparison of the Effectiveness of Combined Diode Laser and GLUMA Bonding Therapy With Combined Diode Laser and 5% Sodium Fluoride Varnish in Patients With Dentin Hypersensitivity: Diode Laser vs GLUMA in Dentin Hypersensitivity - Asna Ashari , Mohammad; Berijani, Amir; Anbari, Fahimeh; Yazdani, Zahra; Zandian, Amin (Journal of Lasers in Medical Sciences, 2021)
Introduction: Dentin hypersensitivity (DH) is one of the most common complaints of patients referred to a dental office, so this study aimed to compare the effectiveness of combined diode laser and GLUMA bonding therapy with combined diode laser and 5% sodium fluoride varnish in patients with DH. Methods: Sixty patients were divided into three groups (bonding, laser-bonding, laser-varnish), and before the intervention, the amount of DH was measured with the visual analog scale (VAS) scale. In the bonding group, GLUMA Desensitizer solution was applied and then air-dried. In the bonding laser group, first bonding was used, and then the affected tooth was irradiated with a diode laser. In the varnish-laser group, 5% sodium fluoride varnish was coated and then the laser was irradiated with the said method. DH was measured immediately after the treatment and then 2, 7 and 30 days after the treatment. Results: Laser-varnish treatment was not different from laser-bonding treatment at all measurement times (P=1). Laser-varnish and bonding treatment were not significantly different up to one week after the intervention, but on the 30th day after the intervention, the difference in pain was significant (P=0.01). There was no significant difference in laser-bonding treatment up to one week after the intervention, but on the 30th day after the intervention, the difference in pain was significant (P=0.003). Conclusion: The combined treatment with GLUMA bonding and the 660 nm diode laser is effective in reducing DH and this is more effective than GLUMA bonding alone in the long term. However, it does not have a significant advantage over the combined varnish-laser method, but it seems that due to its ease of use, it can be a suitable alternative to the varnish-laser method. DOI:10.34172/jlms.2021.62